Cardioprotective Properties of Opioid Receptor Agonists in Rats WithStress-Induced Cardiac Injury; Physiological Research; Vol. 68, iss. 3 - Prokudina E. S. Ekaterina Sergeevna; Maslov L. N. Leonid Nikolaevich; Naryzhnaya N. V. Nataliya Vladimirovna; Tsybulnikov S. Yu. Sergey Yurjevich; Lishmanov Yu. B. Yury Borisovich; Madias J. E. John; Oeltgen P. R. Peter (2019, 2019)
Title screen